Benefits of Company Management Systems with Combination of ERP (Enterprise Resource Planning) - Richa Afriana Munthe (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to determine the advantages of implementing a company management system with a combination of ERP in a company. The type of research used is a literature review. In this study, in the administrative control process, the ERP framework can be a facilitator in carrying out the administrative control process. For the preparation and planning process. The advantages of using an ERP framework combine the organizational lines of a coordinated business framework, extending the effectiveness and usefulness of the organization, disclosing precise detailed information and making controlled preparations. As a result of this research, there are several modules in the ERP framework, such as FI (Financial Bookkeeping), which are designed to provide a continuous estimate of an organization's revenue and measure an organization's financial performance against internal and external exchanges. information. Using the FI module, administrators can screen and examine an organization's financial exhibits that show how well the organization's faculty and staff are performing in extending benefits. The advantages of using an ERP framework combine organizational lines of a coordinated business framework, extending organizational effectiveness and usability, accurate disclosure of details, and controlled preparation.